2018
DOI: 10.1108/jfp-10-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Psychological trauma in professionals working with traumatised children

Abstract: Practical implications:Various implications are noted from this review. These include the importance of education and support for staff, to be mindful that newer staff may be considered an 'at risk' group for the negative impact of such trauma, and to encourage staff in achieving an effective work-life balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Those with a higher proportion of traumatized clients or more time spent with trauma survivors may be at greater risk for experiencing these difficulties (Hensel et al 2015 ). Although numerous empirical studies have documented the nature, prevalence, and impact of the stressors experienced by mental health clinicians working with trauma survivors (Bride 2007 ; Creamer and Liddle 2005 ; Cunningham 2003 ; Hamama 2012 ; Ireland and Huxley 2018 ), a systematic review of the empirical literature found minimal research on interventions designed to prevent and/or ameliorate the stressful effects of this work on the clinicians delivering therapy to this vulnerable population (Bercier and Maynard 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those with a higher proportion of traumatized clients or more time spent with trauma survivors may be at greater risk for experiencing these difficulties (Hensel et al 2015 ). Although numerous empirical studies have documented the nature, prevalence, and impact of the stressors experienced by mental health clinicians working with trauma survivors (Bride 2007 ; Creamer and Liddle 2005 ; Cunningham 2003 ; Hamama 2012 ; Ireland and Huxley 2018 ), a systematic review of the empirical literature found minimal research on interventions designed to prevent and/or ameliorate the stressful effects of this work on the clinicians delivering therapy to this vulnerable population (Bercier and Maynard 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Professionals should be supported to take regular breaks between their clients and use this time to process this material. Not exceeding the hours of work and ensuring a work-life balance is vital for professionals to avoid the impact of ongoing vicarious exposure to trauma and promote growth ( Ireland & Huxley, 2018 ). These are important characteristics that all organisations could consider, particularly at a time when meeting the growing demand on mental health services may compromise the level of commitment to professional well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The pertinence of this issue is increased, considering the current support for trauma-informed approaches that promote awareness of power imbalances in caring relationships (Johnstone, et al 2018;Cleary & Hungerford, 2015;Bateman, Henderson, & Kezelman, 2013). An understanding of team psychodynamics is therefore needed, to support relational ways of working with Individuals accessing services and to promote better care outcomes, particularly with those Individuals experiencing crisis or who are considered 'stuck' in treatment (Huxley & Ireland, 2018).…”
Section: Introductionmentioning
confidence: 99%